A revised FMEA with application to a blow moulding process. Issue 7 (1st August 2016) - Lolli, Francesco; Gamberini, Rita; Rimini, Bianca; Pulga, Francesco
Abstract : Purpose: – The purpose of this paper is to present a modified failure mode and effects analysis (FMEA) in order to make the assignment of the scores for the occurrence factor more robust, and to link the FMEA chart directly to the maintenance activities. Design/methodology/approach: – A well-known clustering algorithm (i.e. K-means), along with a normalisation approach, are applied and compared for the assignment of the occurrence scores. Subsequently, the relationship between failures and maintenance operations is made explicit by a correlation matrix. Finally, the K-means algorithm is applied to the maintenance operations again in order to sort them into priority classes. Findings: – It is found that this revised FMEA approach improves the standard one due to its more rigorous mathematical formulation and lean applicability in real operating environments. Research limitations/implications: – The novel approach may be improved by a deeper statistical analysis and/or applying the fuzzy theory. Practical implications: – A real case study is introduced in order to show the applicability of this approach to the quality control of a blow moulding process. It is found that this approach reveals a high potentiality for dealing with real issues. Originality/value: – The paper provides a further step towards bridging the gap between theory and practical application of the FMEA approach.